2023 round tables on AI and the global news industry - Cecil, J (Reuters Institute for the Study of Journalism, 2024)
This paper reflects on three Round Tables held across 2023 by the Reuters Institute to consider the growing impact of emerging AI technology on the creation of news. Participants included global news organisations, tech platforms and disinformation detection companies. News organisations were very willing to experiment with AI tools and appreciated that the playbook for using AI would have to come from their trials. Participating Global South publishers were already conducting these experiments at scale, but faced a stark risk/benefit trade off, as the boldest moves to use AI cut costs and open markets but come with risks that can’t yet be mitigated. Nevertheless, all publishers stand to gain from this experimentation. All participants were interested in technical advances to fight AI-enabled disinformation. Many news organisations considered Intellectual Property top of mind when considering AI and were concerned their interests did not align with those of tech platforms